Compressive Behavior and Microstructural Characteristics of Iron Hollow Sphere Filled Aluminum Matrix Syntactic Foams - Szlancsik, Attila (Materials (Basel), 2015)
Iron hollow sphere filled aluminum matrix syntactic foams (AMSFs) were produced by low pressure, inert gas assisted infiltration. The microstructure of the produced AMSFs was investigated by light and electron microscopy, extended by energy dispersive X-ray spectroscopy and electron back-scattered diffraction. The investigations revealed almost perfect infiltration and a slight gradient in the grain size of the matrix. A very thin interface layer that ensures good bonding between the hollow spheres and the matrix was also observed. Compression tests were performed on cylindrical specimens to explore the characteristic mechanical properties of the AMSFs. Compared to other (conventional) metallic foams, the investigated AMSFs proved to have outstanding mechanical properties (yield strength, plateau strength, etc.) and energy absorbing capability.